Site-selective modification of peptides using rhodium and palladium catalysis: complementary electrophilic and nucleophilic arylation. - Chapman, C; Matsuno, A; Frost, C; Willis, M (2007)
The site-selective modification of peptides containing dehydroalanine, tyrosine and tryptophan residues has been achieved using rhodium catalysed conjugate additions or palladium catalysed aryl-amination and -etherification reactions.